Comparison of Recurrence Rate Between Re-Excision With Radiotherapy and Radiotherapy-Only Groups in Surgical Margin Involvement of In Situ Carcinoma - Lee, Jun-Hee; Lee, Hyunjun; Bang, Yoon Ju; Ryu, Jai Min; Lee, Se Kyung; Yu, Jonghan; Lee, Jeong Eon; Kim, Seok Won; Nam, Seok Jin; Chae, Byung Joo (Journal of breast cancer, 2022)
Surgical margin status is a surrogate marker for residual tumors after breast-conserving surgery (BCS). A comparison of ipsilateral breast tumor recurrence (IBTR) rates between re-excision combined with radiotherapy (excision with RTx) and RTx alone, following the confirmation of ductal carcinoma in situ (DCIS) in the resection margin after BCS, has not been reported previously. Therefore, in the present study, the clinical characteristics of DCIS involvement in the surgical resection margin between excision with RTx and RTx alone were investigated, and the IBTR rate was compared.PURPOSESurgical margin status is a surrogate marker for residual tumors after breast-conserving surgery (BCS). A comparison of ipsilateral breast tumor recurrence (IBTR) rates between re-excision combined with radiotherapy (excision with RTx) and RTx alone, following the confirmation of ductal carcinoma in situ (DCIS) in the resection margin after BCS, has not been reported previously. Therefore, in the present study, the clinical characteristics of DCIS involvement in the surgical resection margin between excision with RTx and RTx alone were investigated, and the IBTR rate was compared.We analyzed 8,473 patients treated with BCS followed by RTx between January 2013 and December 2019. Patients were divided into 2 groups based on surgical resection margin status in permanent pathology, and superficial and deep margins were excluded. Patients who underwent re-excision with DCIS confirmed in the resection margin were identified and the IBTR rate was examined.METHODSWe analyzed 8,473 patients treated with BCS followed by RTx between January 2013 and December 2019. Patients were divided into 2 groups based on surgical resection margin status in permanent pathology, and superficial and deep margins were excluded. Patients who underwent re-excision with DCIS confirmed in the resection margin were identified and the IBTR rate was examined.Among 8,473 patients treated with BCS, 494 (5.8%) had positive surgical resection margins. The median follow-up period was 47 months. Among the 494 patients with a positive resection margin, 368 (74.5%) had residual DCIS at the surgical resection margin in the final pathology. Among those with confirmed DCIS at the resection margin, 24 patients (6.5%) were re-excised, and 344 patients (93.5%) underwent RTx after observation. The IBTR rates were 4.2% and 1.2% in the re-excision and observation groups, respectively. IBTR-free survival analysis revealed no significant difference between the excision with RTx and RTx-only groups (p = 0.262).RESULTSAmong 8,473 patients treated with BCS, 494 (5.8%) had positive surgical resection margins. The median follow-up period was 47 months. Among the 494 patients with a positive resection margin, 368 (74.5%) had residual DCIS at the surgical resection margin in the final pathology. Among those with confirmed DCIS at the resection margin, 24 patients (6.5%) were re-excised, and 344 patients (93.5%) underwent RTx after observation. The IBTR rates were 4.2% and 1.2% in the re-excision and observation groups, respectively. IBTR-free survival analysis revealed no significant difference between the excision with RTx and RTx-only groups (p = 0.262).The IBTR rate did not differ between the excision with RTx and RTx-only groups when DCIS was confirmed at the resection margins. This suggests that RTx and close observation without re-excision could be an option, even in cases where minimal involvement of DCIS is confirmed on surgical resection.CONCLUSIONThe IBTR rate did not differ between the excision with RTx and RTx-only groups when DCIS was confirmed at the resection margins. This suggests that RTx and close observation without re-excision could be an option, even in cases where minimal involvement of DCIS is confirmed on surgical resection.